Dr. E. Ted Chandler - (:unkn) unknown (Wake Forest University, 2009)
Info from OH# 1044; Topics, June 1982
Dr. E. Ted Chandler grew up in the Baptist Children’s Orphanage and received the Morehead Scholarship that paid for his medical education at UNC Chapel Hill. After graduating he did his internship and one-year of residency at North Carolina Baptist Hospital. He went into Family Medicine in 1955 and also ran the Emergency Room at NCBH from 1965-66. In 1976, Dr. Chandler accepted the position as Medical Director of Reynolds Health Center.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth